Pengaruh Kurikulum Merdeka Terhadap Kecerdasan Interpersonal Siswa Kelas IV SDIQ Ar-Risalah Lubuklinggau - Ayu Meirani (Prodi PGMI Universitas Islam Nusantara Al-Azhaar Lubuklinggau, 2025)
Interpersonal intelligence is a skill that students must have in preparing themselves to face the era of revolution that encourages an ability to be able to work together in groups and individuals. In this case, the future goal of implementing the independent curriculum at SDIQ Ar Risalah can improve students' interpersonal intelligence. This research is a quantitative form carried out at SDIQ Ar Risalah Luuklinggau. Data collection uses observation, questionnaires or questionnaires and documentation methods. The population is all fourth-grade students of SDIQ Ar Risalah Lubklinggau. The sample is 90 fourth-grade students and 4 class teachers. The results of this study can be concluded that the implementation of the independent curriculum on the interpersonal intelligence of fourth-grade students of SDIQ Ar Risalah Lubuklinggau with a score of 69 is in the good category. interpersonal intelligence of fourth grade students at SDIQ Ar Risalah Lubuklinggau with a sample of 90 people, it is known that 65 students were declared high interpersonal intelligence and 25 students were found to be low with an average value of 31.38 and a standard deviation value of 3,716. The influence of the independent curriculum on students' interpersonal intelligence is 54%, with a value of -0.253 in the very weak category. The principal and educators are expected to work together to create a learning or training activity that becomes a place to improve interpersonal intelligence in the independent curriculum in students.